KORELASI ANTARA VOLUME INFARK DAN AKTIFITAS KEHIDUPAN SEHARI-HARI PADA PASIEN STROKE INFARK - , Maria Agustina Dewanti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Stroke is characterized by the sudden loss of blood circulation to an area of the brain, resulting in a corresponding loss of neurologic function. Broadly, strokes are classified as either hemorrhagic or ischemic. It is difficult to be sure clinically about the type of stroke in majority of cases as there is no specific differentiating feature. Infarct stroke can cause functional disability, in patient with infarct stroke functional disability can be seen in Activities of Daily Living (ADL). Activities of Daily Living (ADL) is a term used in healthcare to refer to daily selfcare activities within an individual's place of residence, in outdoor environments, or both. CT scan is a standard of care in stroke imaging. Volumetric estimations of cerebral infarctions can be estimated by MSCT and their prognostic value have been studied widely. Lesion volumes have been shown to correlate with clinical outcomes. Methods: This study was a cohort observational non experimental study. The study population consisted of 54 patients with infarct stroke, admission in Dr. Sardjito Central General Hospital between October 2011 and February 2012 (according to inclusion and exclusion criteria). Collected data was proccessed and statistically analyzed using correlation test ( Spearman) with p < 0,05. Correlation between factors, other than infarct volume and ADL will be analyzed using multivariate analysis. Volume infarct thought to be significantly correlated positively with Activities of Daily Living in patient infarct stroke. Result: The infarct volume corrrelated negatively with Activities of Daily Living (ADL). Activities of Daily Living (ADL) which is represented by Barthel Index score II measured one month after stroke (r = 0,358 dan p = 0,070 ). Conclusion: There is no significantly positive correlation between infarct volume and activities of daily living in infarct stroke in one month observation of Barthel Index II. The multivariate analisis linear regresion showed there is no significancy correlation between these variable variable with Barthel Index score II measured one month after stroke.